Feminist (re)writing. Notes on Begoña Caamaño - Nogueira Pereira, María Xesús (Madrygal. Revista de Estudios Gallegos, 2016)
An approach to the author Begoña Caamaño (1964-2004) dealing with both her biographical and intellectual profile as well as the main keys to her narrative project. This paper also aims to place the writer in context with contemporary Galician narrative, in particular with feminist writing of the last decades.